2016
DOI: 10.1177/0193945916683399
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Daily Weighing Among Successful Weight Loss Individuals During a 12-Month Weight Loss Study

Abstract: The purpose of the study was to describe participants' experience of daily weighing and to explore factors influencing adherence to daily weighing among individuals who were successful in losing weight during a behavioral weight loss intervention. Participants completed a 12-month weight loss intervention study that included daily self-weighing using a Wi-Fi scale. Individuals were eligible to participate regardless of their frequency of self-weighing. The sample ( N = 30) was predominantly female (83.3%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 26 publications
4
16
0
Order By: Relevance
“…Results indicate that when observing the sample as a whole, participation in a weight loss intervention, especially the weight loss phase, increased positive beliefs and decreased negative beliefs about weight self-monitoring behavior, although this effect was stronger in the more intensive version of the intervention. Consistent with previous qualitative findings, results suggest that participants find that self-weighing is not as frustrating as expected, and that it can be helpful and positive in achieving goals after engaging in an intervention promoting daily self-weighing (19).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results indicate that when observing the sample as a whole, participation in a weight loss intervention, especially the weight loss phase, increased positive beliefs and decreased negative beliefs about weight self-monitoring behavior, although this effect was stronger in the more intensive version of the intervention. Consistent with previous qualitative findings, results suggest that participants find that self-weighing is not as frustrating as expected, and that it can be helpful and positive in achieving goals after engaging in an intervention promoting daily self-weighing (19).…”
Section: Discussionsupporting
confidence: 86%
“…Approximately 60% of active duty personnel are affected by overweight and obesity, which is a critical concern for the U.S. military (22). This diverse population of military personnel provided a unique opportunity to examine race differences as well as gender differences dissimilarly from previous studies, which have examined primarily female samples (3,13,14,19).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, even though participants only rarely engaged in action planning, their behaviour was still influenced by the weighing to some extent. This corresponds to findings by Zheng et al (2018), whose participants stated that the prospect of weight loss and observing weight loss motivated them to continue with weight loss behaviours. Similarly, studies from a laboratory setting have shown that weighing oneself significantly reduces subsequent snack consumption (Gupta, Wang, Corona, & Levitsky, 2017).…”
Section: Experiences With Daily Weighingsupporting
confidence: 83%
“…Our qualitative analysis showed that weighing elicited emotional reactions. Similarly, a qualitative study by Zheng and colleagues, investigating the experiences with self-weighing in a weight loss trial, also found that participants reported feelings of frustration when expected weight loss did not materialise, and positive emotions when weight measurements were lower than expected (Zheng et al, 2018). Some of our participants found the intensity of their emotional reaction excessive.…”
Section: Experiences With Daily Weighingsupporting
confidence: 67%
“…Research has shown that daily self‐weighing (DSW) could play an important role in weight maintenance following weight loss, although this is often done in conjunction with other behavior modifications, making it difficult to attribute success solely to DSW . When investigated as the only weight management intervention, a study in adults with obesity showed that DSW can produce clinically significant weight loss .…”
Section: Introductionmentioning
confidence: 99%